The relationship between social support and interpersonal self-efficacy among higher vocational college students: parallel mediation effects of anxiety and loneliness - Chunmei Chen; Yujie Zhu; Yanyan Sun; Mingkun Que (BMC Psychology)
Abstract Background There is close cooperation between higher vocational colleges and enterprises. Thus, higher vocational college students attach great importance to the internship experience in enterprises during their study period. They need to have more interaction and communication with school teachers, classmates and enterprise staffs, etc. Their interpersonal self-efficacy is important for developing and maintaining their good interpersonal relationships. Method To explore the effect of social support on the interpersonal self-efficacy of higher vocational college students and the parallel mediating role of anxiety and loneliness in it, a questionnaire survey and empirical analysis was conducted on 4,270 Chinese higher vocational college students by using the Social Support Scale for Adolescents, Interpersonal Communication Self-efficacy Scale for College Student, Self-rating Anxiety Scale and UCLA Loneliness Scale. Results (1) social support significantly and positively predicts interpersonal self-efficacy; (2) social support influences interpersonal self-efficacy through the mediating effect of anxiety; and (3) social support influences interpersonal self-efficacy through the mediating effect of loneliness. Conclusions This study contributes to the understanding of the underlying mechanisms of the relationship between social support and interpersonal self- efficacy, thus providing references for higher vocational institutions and other related sectors to improve the interpersonal self-efficacy of higher vocational college students.